Modified Continuous Loop Technique for microvascular anastomosis - P Kumar; K G Bhaskara; P C Thomas (Indian Journal of Plastic Surgery)
A modified method of continuous loop technique for microvascular anastomosis is described. The handling of loop is easier & even last suture is placed under vision. This makes the microvascular anastomosis easier and simpler.